The 20th-Century Theatre Avant-Garde vs. the Circus (Not just the Clown and the Tiger. Sketches about Circus Arts, 2019)
Initiating the process of theatre revival at the beginning of the 20th century, the reformers of the theatre art drew from many sources. Along with the visual arts, film, avant-garde literature, they also restored the relationship of the theatre with other forms of spectacles, including the circus. Theatre makers used some elements of the circus show to define the theatrical space, composition of the performance, acting techniques and the spectator-viewer relationship anew. The article is a review of the avant-garde theatre practices that refer to the circus. The impact of the circus on the arrangement of theatrical space and the formation of the arena scene has been indicated, for example in Max Reinhardt’s practice, Walter Gropius and Farkas Molnar’s projects in the Bauhaus and in the theatre designed for Meyerhold’s Vsevolod. The circus composition is also seen in the Bauhaus productions, especially in Laszlo Moholy Nagy’s or Futurists’ projects and Erwin Piscator’s revues. On the other hand, the reference to the circus performing techniques can be found in the Bauhaus ‒ especially in Oskar Schlemmer’s production, as well as in Meyerhold’s biomechanics or the reserved acting in the performances by Bertolt Brecht.